Xác định ranh giới F/F trên các hệ tầng đá vôi tại xóm Nha, Quảng Bình bằng phương pháp MSEC - Lan, Lưu Thị Phương; Ellwood, B. B.; Phương, Tạ Hòa (Vietnam Journal of Earth Sciences, 2007)
Placement of the Frasnian-Famennian (Upper Devonian) extinction event and boundary within the Xom Nha section, Middle Vietnam, using newbiostratigraphic (Conodont) and magnetostratigraphic (susceptibility) data